Social infrastructure as a socio-geographical category - Kostashchuk, Ivan; Kolosivskyi, Nazarii (Human Geography Journal, 2024)
The modern period is characterized by significant changes in all spheres of life. Previously known phenomena acquire a new meaning. Accordingly, there is a need to rethink and clarify many concepts, including social infrastructure. Despite the fact that it is of considerable interest to representatives of various sciences, today there is no comprehensive understanding of its essence. The literature is often characterized by ambiguity in the interpretation of this concept, which leads to confusion in its use. The article considers the universal category “infrastructure,” which is used to explain various economic and social processes. Attention is paid to approaches to its understanding. It is noted that there are different types of infrastructure: information, innovative, institutional, market, ecological, military and others, but one of the most popular is the division of infrastructure into industrial and social. Three stages of formation of the term “social infrastructure” are mentioned. The evolution of its content is analyzed and four main trends are identified: 1) the economic character of the social infrastructure at the initial stage; 2) a shift in views towards meeting the needs of the population and ensuring proper living conditions; 3) assigning one of the leading roles to the social infrastructure in the comprehensive development of the individual; 4) digitalization of social infrastructure. Approaches to the interpretation of this term are generalized by reducing them to two main ones: sectoral and material. The essence of social infrastructure is revealed. The author’s definition of this concept is proposed, according to which social infrastructure is the material basis necessary to create favorable conditions for normal life and development of society. It includes both physical (organizations, institutions, buildings, public spaces, etc.) and digital (online platforms, services, websites, applications, etc.) objects. It is emphasized that when conducting geographical research, its territorial and spatial aspect should be taken into account. Regional socio-geographical studies of social infrastructure are particularly promising.